Metabolomic and metagenomic analyses elucidate the role of intercropping in mitigating continuous cropping challenges in tobacco - Liu, Ming; Xue, Rujun; Jin, Shuangzhen; Gu, Kaiyuan; Zhao, Jie; Guan, Shuyue; Xie, Xiaoyu; Su, Jiaen; Wang, Longchang (Frontiers in Plant Science, 2024)
Crop rotation of tobacco with other crops could effectively break the negative impact of continuous tobacco cropping, but the mechanisms of intercropping system effects on tobacco, especially on the rhizosphere, are not clear. In this study, we investigated the impact of intercropping system on the diversity and function of tobacco metabolites and microorganisms through metabolomic and metagenomic analyses of the tobacco rhizosphere microenvironment intercropped with maize and soybean. The results showed that the contents of huperzine b, chlorobenzene, and P-chlorophenylalanine in tobacco rhizosphere soils differed significantly among soybean-tobacco and maize-tobacco intercropping system. Chlorobenzene and P-chlorophenylalanine had the highest relative abundance under the soybean-tobacco intercropping system, and huperzine b had the highest relative abundance in the maize-tobacco cropping system. At the phylum level, the three most dominant strains were the same across all treatments: Proteobacteria, Actinobacteria, and Acidobacteria, with only minor differences in their abundance, with the fourth most abundant strain in both the tobacco monoculture. KEGG enrichment analysis of the tobacco rhizosphere soil microbiome revealed that intercropping significantly increased the abundance of metabolites in the ABC transporters pathway and up-regulated the LivK, LivH, Livg, LivM, and LivF genes of the branched-chain amino acid pathway. Collectively, our results indicate that the intercropping could enhance the activity of Livs to enhance the ABC transport pathway, and thus improve the transmembrane transport ability of tobacco roots, thus reducing the negative impact of continuous tobacco cropping. At the same time, the maize-tobacco intercropping could promote the production and transportation of phenolic acids, flavonoids, and other bioactive substances in the tobacco root system, which could enhance tobacco adaptation capacity to abiotic stress.